2017
DOI: 10.1094/pdis-11-16-1667-re
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Variability of Meloidogyne incognita Populations Occurring in Pepper-Production Greenhouses in Israel Toward Me1, Me3 and N Pepper Resistance Genes

Abstract: Natural variation in the root-knot nematode Meloidogyne incognita is problematic for breeding programs: populations possessing similar morphological characteristics can produce different reactions on the same host. We collected 30 widely dispersed M. incognita populations from protected pepper production systems in major pepper-growing regions of Israel and accurately identified their virulence characteristics by modified differential host test in a growth chamber on tomato, tobacco, cotton, melon, pepper, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 23 publications
0
10
1
1
Order By: Relevance
“…be resistant to the nematode. It has been reported that the resistance mediated by the Me1 gene to M. incognita was more durable than that mediated by Me3 or the N gene (Sánchez-Solana et al, 2016;Bucki et al, 2017). Our greenhouse data showed that M. incognita slightly reproduced (RF = 0.9) on HDA-330 (Me1), though it was not statistically greater than the other resistant lines.…”
Section: Resistant Pepper Have Different Effects On Meloidogyne Penetration and Reproductioncontrasting
confidence: 48%
See 2 more Smart Citations
“…be resistant to the nematode. It has been reported that the resistance mediated by the Me1 gene to M. incognita was more durable than that mediated by Me3 or the N gene (Sánchez-Solana et al, 2016;Bucki et al, 2017). Our greenhouse data showed that M. incognita slightly reproduced (RF = 0.9) on HDA-330 (Me1), though it was not statistically greater than the other resistant lines.…”
Section: Resistant Pepper Have Different Effects On Meloidogyne Penetration and Reproductioncontrasting
confidence: 48%
“…Our greenhouse data showed that M. incognita slightly reproduced (RF = 0.9) on HDA-330 (Me1), though it was not statistically greater than the other resistant lines. Populations of M. incognita have been reported to break resistance in pepper lines carrying the Me3 and N gene (Castagnone-Sereno et al, 2001;Piedra Buena et al, 2005;Thies, 2011). The M. arenaria-resistant pepper lines Charleston Belle, HDA-149, HDA-330, PM-217, and PM-687 exhibited high resistance to M. arenaria race 1.…”
Section: Resistant Pepper Have Different Effects On Meloidogyne Penetration and Reproductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different amounts of fresh leaves of B. pilosa (20g, 40g, 60g, 80g, and 100g) were incorporated into the soil during sowing and each treatment was replicated in four pots. The control pots and the pots with B. pilosa leaves were all be supplied with 500ml tap water daily according to procedure by Bucki, et al [13] …”
Section: Growth Experimentsmentioning
confidence: 99%
“…In pepper, at least 10 dominant genes, Me1 to Me7 , Mech1 , Mech2 and N have been reported to confer resistance to Meloidogyne spp. (Wang and Bosland, 2006; Djian-Caporalino et al, 2007; Wang et al, 2009; Bucki et al, 2017). Me1 , Me3 , Me7 , and N confer resistance to a wide range of RKNs, including M. arenaria , M. javanica , and M. incognita .…”
Section: Introductionmentioning
confidence: 99%